Effects of boundary conditions in dynamic tests for pedestrian safety: a finite element simulation study. (20th April 2009) - Soni, Anurag; Mukherjee, Sudipto; Chawla, Anoop
Dynamic impact tests on post mortem human subjects (PMHSs) have been used to understand the injury mechanism and to devise countermeasures for pedestrian safety. Available experimental studies of impacts to the lower limbs simulating those encountered in automobile crashes is limited in number. However, the current European and Japanese standards have been devised from such tests. These tests have a degree of uncertainty associated with their boundary conditions due to the dynamic loading which are difficult to quantify during the test and hence usually not reported. This can lead to the erroneous results. It is concluded that the experiments should be designed to limit the effect of such dynamics based parameters or the final results should be compensated/normalised for the dynamic loading.